Protecting and safeguarding children in schools : a multi-agency approach - Baginsky, Mary (Bristol University Press, 2022)
Schools play a vital role in safeguarding children and young people, and this timely book examines how schools identify and respond to child protection concerns, and their engagement with local authority children's services.